2014
DOI: 10.1159/000358297
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood-Brain Barrier Permeability on Perfusion Computed Tomography Predicts Hemorrhagic Transformation in Acute Ischemic Stroke

Abstract: Background/Purpose: Perfusion computed tomography (CT) is capable of measuring the permeability surface product (PS). PS reflects the permeability of the blood-brain barrier, involved in the pathophysiology of hemorrhagic transformation (HT) of ischemic stroke. The aim of our study was to determine if an increased PS can predict HT. Methods: A total of 86 patients with ischemic stroke were included. They underwent multimodality CT, including the measurement of PS. We compared the clinical and radiological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 70 publications
1
53
1
1
Order By: Relevance
“…Several papers also describe a predictive value of BBBP measurements [19-21, 32, 33]. The acquisition and post-processing techniques of assessing BBBP is different in all papers, which makes direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers also describe a predictive value of BBBP measurements [19-21, 32, 33]. The acquisition and post-processing techniques of assessing BBBP is different in all papers, which makes direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of the blood-brain barrier (BBB) has been implicated in HT occurrence and can be measured with CTP [18-21]. This is based on the assumption that leakage of contrast agent into the extravascular space may indicate a disrupted BBB that may more likely evolve into a HT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool can prospectively stratify patients into those who will or will not go on to develop hemorrhagic conversion using a PS threshold of 0.23 mL/min/100 g [57]. Another study observed an odds ratio of 28 for hemorrhagic transformation discriminating with a PS of >0.84 mL/100 g/min [58].…”
Section: Blood-brain Barrier (Bbb) Permeabilitymentioning
confidence: 99%
“…Computed tomography (CT) is the routine clinical test in cases of stroke and has been used to study the occurrence and effect of BBB dysfunction in ischemic stroke (4,3032). Specifically, dynamic contrast-enhanced CT (DCE-CT) can be used to measure vessel permeability and has been used to correlate BBB dysfunction to post-stroke complications such as hemorrhagic transformation and malignant edema (31,33). …”
Section: Introductionmentioning
confidence: 99%